Review of the detasseling techniques for maize (Zea mays L.) hybrid seed production - Zhang, Ruirui; Yang, Jiaxuan; Chen, Liping; Ding, Chenchen; Li, Longlong; Zhang, Linhuan (International Journal of Agricultural and Biological Engineering, 2024)
Maize (Zea mays L.) is a critical staple crop globally, integral to human consumption, food security, and agricultural product stability. The quality and purity of maize seeds, essential for hybrid seed production, are contingent upon effective detasseling. This study investigates the evolution of detasseling technologies and their application in Chinese maize hybrid seed production, with a comparative analysis against the United States. A comprehensive examination of the development and utilization of detasseling technology in Chinese maize hybrid seed production was undertaken, with a specific focus on key milestones. Data from the United States were included for comparative purposes. The analysis encompassed various detasseling methods, including manual, semi-mechanized, and cytoplasmic male sterility, as well as more recent innovations such as detasseling machines, and the emerging field of intelligent detasseling driven by unmanned aerial vehicles (UAVs), computer vision, and mechanical arms. Mechanized detasseling methods were predominantly employed by America. Despite the challenges of inflexible and occasionally overlooked, applying detasseling machines is efficient and reliable. At present, China’s detasseling operations in hybrid maize seed production are mainly carried out by manual work, which is labor-intensive and inefficient. In order to address this issue, China is dedicated to developing intelligent detasseling technology. This study emphasizes the critical role of detasseling in hybrid maize seed production. The United States has embraced mechanized detasseling. The application and development of manual and mechanized detasseling were applied later than those in the United States, but latest intelligent detasseling technologies first appeared in China. Intelligent detasseling is expected to be the future direction, ensuring the quality and efficiency of hybrid maize seed production, with implications for global food security. Keywords: detasseling technique, detasseling machine, UAVs, intelligent agriculture, maize hybrid seed productionDOI: 10.25165/j.ijabe.20241703.8423Citation: Zhang R R, Yang J X, Chen L P, Ding C C, Li L L, Zhang L H. Review of the detasseling techniques for maize (Zea mays L.) hybrid seed production. Int J Agric & Biol Eng, 2024; 17(3): 1-11.